Molecular subtyping of Blastocystis sp. detected in patients at a large tertiary referral hospital in Lusaka, Zambia - Munsaka, Gilbert; Hayashida, Kyoko; Mubemba, Benjamin; Simulundu, Edgar; Mulunda, Namwiinga; Pule, Ruth; Sianongo, Sandie; Makuluni, Marina; Muleya, Walter; Changula, Katendi; Chitanga, Simbarashe; Mutengo, Mable (Frontiers in Parasitology, 2022)
Background Blastocystis sp. is a common enteric eukaryote of humans whose pathogenicity is still debatable. However, a number of reported infections associated with enteric disease exist. In Zambia, presence of the pathogen has previously been reported in children. However, the molecular epidemiology of Blastocystis infections remain unclarified in Zambia. Methods & Results Archived stool samples submitted for routine parasitological diagnosis at Zambia’s largest tertiary referral hospital positive for Blastocystis sp. by microscopic examination were selected for the study. Subtyping of the Blastocystis was done based on PCR amplification, sequencing and subsequent phylogenetic analysis of the 18S small subunit (SSU) rDNA gene. Four subtypes, ST1 (allele 4), ST2 (allele 12), ST3 (allele 34, 36, 37, 38, 39) and ST6 (allele 122), were identified by molecular procedures in the study, with some Zambian sequences showing close relationships with those detected in non-human primates and common rats. Conclusions The study revealed the circulation of multiple Blastocystis subtypes ST1, ST2, ST3 and ST6 in the study population. The close clustering of some Zambian sequences with those detected from animals suggests the possibility of the presence of both anthroponotic and zoonotic transmission cycles in the country. Further studies in animal populations are recommended for a better understanding of the epidemiology of Blastocystis and for implementation of effective evidence-based control strategies.